ANALISIS KESALAHAN GRAMATIK PADA KETRAMPILAN MENULIS KARANGAN SEDERHANA SISWA KELAS X SMA NEGERI 1 TAMAN - FRANSISKA BENEDIKTA S. D., MARIA (LATERNE, 2016)
When learning about foreign language we are force to not jut know how to use it but also to completely understand the rules in that language. Student are tend to have a problem to arrange sentence. Based on survey result on students X IPS 3 SMA Negeri  1 Taman that has been done found that some grammatical mistakes on writing an essay. The essay is part of writing activity. By looking at it, this research purpose was to descripting mistake of language aspect such as ortograpy,morphology,and syntax in German language writing of students X IPS 3 SMA Negeri 1 Taman. In this research use a descriptive qualitative because this research which has purpose to understanding everything has  occur by the subject of research, like behavior and act which descripted in form of words, sentence,and language, in some special context which happen naturally by using natural method. This research instrument is test, data gather is done using documentation technic. After the data has analyzed we can conclude that there are a lot mistakes on ortography subject and conjugation mistake. The cause that make this mistake occur is performancy and competency factor, and the source that make this mistake occur is interference and intralingual. Key word : grammatical mistake, writing ability